Peran Dinas Pariwisata Dalam Tata Kelola Dan Promosi Kawasan Pariwisata (Studi Kasus di Kecamatan Pemenang Kabupaten Lombok Utara) - M. Taufik Rachman; Baiq Reinelda Tri Yunarni (Universitas Muhammadiyah Mataram, 2019)
The strategy of developing tourism promotion is much done by developing countries is to strengthen the national economy. The tourism industry sector is believed to be a sector in building the economy towards progress. The problem is how the Tourism Office manages tourist attractions that must be solved. The existence of the Office of Tourism in an area will certainly affect the economy by absorbing workers in tourist attractions and surrounding communities. Likewise with the existence of the Tourism Office in Pemenang Subdistrict which is able to help the community around its place of business by providing land / space for pokdarwis members' business activities and providing funds or training for pokdarwis in accordance with the business sector being run. Thus, there will be a significant influence on the workforce or the community if it has been found how much the workforce is absorbed by the Tourism Office in the winning sub-district. And to improve the welfare of the community in an area, the role of the Tourism Office is very much needed in an effort to participate in building and developing the tourism sector in the region and at the national level.